Experience with Brands and Perceived Quality in Most Remembered Medicines - FERREIRA NETO, MACÃRIO NERI; CASTELO, JOSE SARTO FREIRE; CASTRO, JÉSSYCA LAGES DE CARVALHO (Revista de Negócios, 2021)
This work aimed to analyze a customer experience with the brand and if it has a positive effect on the perceived quality of the medicines. The non-probabilistic sample included the participation of 209 individuals, who answered the questionnaire available on the electronic platform regarding Google Forms through social networks. To meet the central objective of this study, i.e., to test the hypothesis of the relationship between the experience of the drug brands and the perceived quality, equation modeling was used, even using the PLS-Sem statistical tool. The results achieved demonstrated the existence of a relationship between the experience of the brands with the perceived quality with a positive and predictive average effect, in addition, the results also showed that moderated by gender, the female coefficient increased whereas the male was not significant.